FORMATION AND DEVELOPMENT OF THE INSTITUTE OF CERTIFIED PUBLIC ACCOUNTANTS OF GREECE. - Mattingly, L. A. (The Accounting Review, 1964)
The Institute of Certified Public Accountants of Greece was founded in 1955 by Law No. 3329, which established it not only as a professional association, but also as a practicing firm of Public Accountants. The constitution was formed thus in order to raise the standing of the profession in the face of many adverse conditions. The problems of getting the profession started in Greece may be similar to those in various other countries in which the accounting and auditing profession needs a status lift. The purpose of this paper is to give an account of the rather unique manner in which the profession in Greece has been developed. In the opinion of the author of this article, the manner in which the accounting profession in Greece has been developed has many good practical merits. The regulation of the profession in its early stages of growth helps considerably to ensure that high standards of work are maintained. The strength of the profession is obviously enhanced during this period by a Supervisory Council of prominent citizens whose appointment stems from legal decrees. Theoretical education in auditing needs some considerable development.